2018
DOI: 10.3390/en11102522
|View full text |Cite
|
Sign up to set email alerts
|

The Way Forward in Quantifying Extended Exergy Efficiency

Abstract: Extended exergy accounting (EEA) is a methodology which estimates the extended exergy cost (EEC) of a product or a service or the extended exergy efficiency (EEE) of a country or economic sector taking into account materials, energy, labour, capital, and environmental impact. The use of EEA results for policy or planning purposes has been hampered by: (1) the lack of data to quantify the EEC of most of the inputs, making it almost impossible to quantify the EEC of a product or service and (2) the lack of a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For obvious reasons, this paradigm is known as "extended exergy analysis", or EEA. Previous studies on its application [22,26,[54][55][56] have provided some interesting results: EEA leads to the calculation of the total amount of primary exergy needed to produce a material or immaterial commodity [22,26,57], i.e., to a thermodynamic cost index. More recently, it has been shown that the application of EEA to a society provides a measure of its "exergy footprint", i.e., of its global resource consumption, which is obviously an indicator of the thermodynamic sustainability of the "system society" (in more proper terms, an indicator of the degree of its unsustainability).…”
Section: Materials and Methods 2: Exergy Analysis Of The Neanderthal mentioning
confidence: 99%
“…For obvious reasons, this paradigm is known as "extended exergy analysis", or EEA. Previous studies on its application [22,26,[54][55][56] have provided some interesting results: EEA leads to the calculation of the total amount of primary exergy needed to produce a material or immaterial commodity [22,26,57], i.e., to a thermodynamic cost index. More recently, it has been shown that the application of EEA to a society provides a measure of its "exergy footprint", i.e., of its global resource consumption, which is obviously an indicator of the thermodynamic sustainability of the "system society" (in more proper terms, an indicator of the degree of its unsustainability).…”
Section: Materials and Methods 2: Exergy Analysis Of The Neanderthal mentioning
confidence: 99%
“…From thermodynamics, exergy is defined as the maximum amount of work that can be generated by a system (including mass and energy flows) once a thermodynamic equilibrium with the environment is achieved [21][22][23][24]. Compared to the energy, the exergy of a system is not conserved [25]. This fact is because of the entropy changes that are caused by physical and chemical conversions that are associated with irreversible processes.…”
Section: Introductionmentioning
confidence: 99%